2012
DOI: 10.1007/s00381-012-1689-9
|View full text |Cite
|
Sign up to set email alerts
|

Success criteria in pediatric neuroendoscopic procedures. Proposal for classification of results after 67 operations

Abstract: A common classification of degrees of success, such as that proposed here, would aid the development of comparative and cooperative studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Recently, some authors have identified risk factors and developed different systems to predict ETV success in children, among which the ETV Success Score (ETVSS) stands out as a reliable method that has been validated by many centers worldwide [2,14,22,24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, some authors have identified risk factors and developed different systems to predict ETV success in children, among which the ETV Success Score (ETVSS) stands out as a reliable method that has been validated by many centers worldwide [2,14,22,24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…Various classification systems are emerging not only to help predict outcome after endoscopic procedures for hydrocephalus, but also to aid in the selection of appropriate patients to maximize positive outcomes 25 42 - 45 …”
Section: Discussionmentioning
confidence: 99%
“…Various classification systems are emerging not only to help predict outcome after endoscopic procedures for hydrocephalus, but also to aid in the selection of appropriate patients to maximize positive outcomes. 25,[42][43][44][45] The most common indication for ETV is aqueductal stenosis, either from congenital narrowing of the aqueduct or obstructive tumors such as tectal gliomas 46 and obstructive cysts. 47,48 Other indications include the fenestration of loculated compartments, 49,50 ventriculoperitoneal shunt malfunction, 26,27 and preresectional ETV for posterior fossa tumors.…”
Section: Hydrocephalusmentioning
confidence: 99%
“…In this group, the proposal for treatment was of closure of MM and VP shunt at the same surgical time. VP shunt was chosen as the method of choice for treating hydrocephalus in these children after considering the benefits and drawbacks of endoscopic third ventriculostomy (ETV) in neonates with MM 12,17,21 .…”
Section: Methodsmentioning
confidence: 99%